Short- and long-term determinants of Indonesia’s rice import: An error correction model approach - Setiawati, Ririt Iriani Sri; Jaenudin, M; Amini, Ary Fauziah; Puspita, Ni Putu Rekha (Jurnal Ekonomi & Studi Pembangunan, 2025)
Indonesia's dependence on rice imports has become a crucial issue in food security. This study examines the determinants of rice imports using an ECM model, analyzing the influence of rice production, exchange rate, domestic rice price, harvested land area, foreign exchange reserves, carbon emissions, and rice consumption in short and long term. The results show that in addition to production and consumption factors, macroeconomic variables such as exchange rates and foreign exchange reserves, as well as environmental factors such as carbon emissions, have a significant role in influencing rice imports. These findings highlight the importance of integrated policies between the agricultural, economic, and environmental sectors to achieve sustainable food security